AB0798 Association between Knee Osteoarthritis and Achilles Tendinopathy. (10th June 2014) - Reitblat, T.; Reitblat, O.; Kalichman, L.
Abstract : Background: In our clinical practice, we noticed that individuals with symptomatic knee osteoarthritis (OA) frequently complain on pain or swelling above Achilles tendon. We found no studies that evaluated association between knee OA and Achilles tendon pathology. Objectives: To explore the association between knee OA and changes in Achilles tendon. Methods: Cross-sectional observational cohort study was performed in Rheumatology Unit, Barzilai Medical Center, Ashqelon, Israel. The convenience sample of 30 knee OA (Kellgren-Lawrence (K-L) score ≥2) female patients complaining on unilateral pain was recruited. For each patient, demographic data, K-L score, sonographic evaluation of femoral cartilage thickness and Achilles tendon width, and Western Ontario and McMaster Osteoarthritis (WOMAC) Index were collected. To evaluate the association between femoral cartilage thickness, K-L score, WOMAC parameters, and Achilles tendon width we used Pearson's correlation and linear regression analysis. Results: Significant association was found between Achilles tendon width and WOMAC total score (r=0.490, p=0.006), pain (r=0.416, p=0.022), and functional (r=0.452, p=0.012) scores (but not stiffness score (r=0.242, p=0.198)) in the affected side. Associations remained significant after adjustment for age and body mass index. No associations between similar parameters were found in the unaffected side. No associations were found between K-L score, cartilage thickness and Achilles tendon thickness in affected and in unaffected sides. No associations were found between K-L score or cartilage thickness (at affected or unaffected side) and any parameters of WOMAC. Conclusions: This is a first study that evaluated the association between knee OA parameters and Achilles tendon width. There are previous studies that found that weakness of quadriceps muscle is associated with knee OA. It is possible that gastrocnemius muscle whose attachments are also proximate the knee joint participates in knee stabilization. Stress forces that are implied on the muscle to stabilize osteoarthritic knee may cause structural changes in Achilles tendon. Interestingly, the Achilles tendon width was associated with pain and function of ipsilateral OA knee, but not with radiographic OA severity score (K-L) and not with cartilage thickness. Therefore, the sense of pain in the affected joint may be not only due to cartilage changes in the affected joint, but also because of simultaneous changes in Achilles tendon. Comprehensive assessment of Achilles tendon should probably be part of routine knee OA evaluation. The findings of this research provide a basis for further studies with larger sample size, and using different study designs. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.1619